2015
DOI: 10.1021/acs.energyfuels.5b01537
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Gasification Activity of Na2CO3 and Comparison with K2CO3 for a High-Aluminum Coal Char

Abstract: The catalytic performance of Na2CO3 for high-aluminum coal gasification was specially investigated, and the effect of the ash constituents in Sunjiahao (SJH) high-aluminum coal char on the catalytic activity of Na2CO3 and a comparison with that of K2CO3 were also studied through steam gasification experiments of SJH char catalyzed by Na2CO3 or K2CO3 carried out using a thermogravimetric analyzer and a fixed-bed reactor at 800 °C, respectively. The results indicate that the steam gasification rates of SJH char … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…The carbon conversion ( X ) was calculated using the following equation: X=m0mtm0m, where m 0 represents the initial mass of the sample before gasification, m t indicates the instantaneous mass of the sample at time t , and m ∞ is the total mass of ash.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon conversion ( X ) was calculated using the following equation: X=m0mtm0m, where m 0 represents the initial mass of the sample before gasification, m t indicates the instantaneous mass of the sample at time t , and m ∞ is the total mass of ash.…”
Section: Methodsmentioning
confidence: 99%
“…Ding et al confirmed that Na 2 CO 3 has excellent catalytic performance for coal pyrolysis and gasification by loading Na 2 CO 3 into coal. Wang and collaborators compared the catalytic activity for coal gasification of the two additives K 2 CO 3 and Na 2 CO 3 and found that the catalytic activity of Na 2 CO 3 is larger than that of K 2 CO 3 . And McKee et al pointed out that alkali metal carbonates are generally the most active catalysts for gasification of coal by CO 2 and H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…under high temperature condition. On the other hand, for the low graphitization degree of coal char, in which oxygen-containing functional groups were present, the interaction followed route (2). The presence of oxygen groups helped to stabilize potassium on the carbon surface [22,23].…”
Section: Tg-ftir Analysismentioning
confidence: 99%
“…However, high temperature and pressure are required in the traditional coal gasification process. These requirements increase the capital and the operating expenses of the process considerably [1,2]. Recently, catalytic gasification has been investigated intensively in view of its advantages of lower operating temperature, higher efficient throughput and better economical performance [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…3 As a representative third-generation gasication technology, catalytic gasication has the potential to achieve efficient coal conversion at a low thermochemical reaction temperatures. [4][5][6] Catalytic gasication research has largely focused on catalyst development; single-component catalysts, composite catalysts, and disposable catalysts are most common. Single-component and composite catalysts have good catalytic effects.…”
Section: Introductionmentioning
confidence: 99%